MUTU DAN SUMBER BENIH KACANG TANAH DI KABUPATEN BOLAANG MONGONDOW - Stanley A. F. Walingkas; Pemmy ., Tumewu; Meity R. Rantung; Jelie V. Porong; Tommy Djoice Sondankh (EUGENIA, 2022)
This research aims to: 1). Knowing the quality of peanut seeds used by farmers in Bolaang Mongondow Regency 2). Knowing the source of peanut seeds used by farmers in Bolaang Mongondow Regency. 3). Obtaining good ways of providing and distributing quality peanut seeds to be planted by farmers in Bolaang Mongondow. The study used a survey method (Stratified Random Sampling) which was carried out in stages: Preliminary survey, survey of quality and source of peanut seeds, In Bolaang Mongondow, Dumoga Barat sub-district (Werdie Agung Village and Doloduo Village), Lolak District (Lolak Induk Village and Lolak Dua Village, West Pasi sub-districts (Wngga and Bintau villages) and Bolaang Timur sub-districts (Ambang and Bolaang villages) Testing the quality of survey results, seed viability, seed vigor, number of pods, weight of pods weight of seeds Data on number of pods, weight of pods weight of seeds were analyzed using analysis variety and 5% BNT test.The results showed that the viability variable, the vigor of the peanut seeds used and planted by farmers from seed sources in Bolaang Mongondow district, both for cultivation and guaranteed seed quality standards were respectively, Dumoga Barat District, Doloduo village , Pasi Barat Subdistrict, Wangga Village and Bolaang Timur Subdistrict, Ambang Dua Village, which had the number of sprouts and v above 80% and high vigor. For the sub-districts of Lolak Desa, Lolak Induk, and Lolak Dua, it cannot be recommended because the number of germination and seed viability is below 80% with low vigor. The number of pods and the weight of pods planted gave the same results for each village. The best seed weight in KT2 (Doloduo Village) 31.77 seed weight, KT5 (Wangga Village) 31.59 seed weight, KT7 (Ambang Dua Village) 31.55 seed weight and KT8 26.86 seed weight.